Evaluation of effect of 25 °API crude oil on produced water corrosiveness with sulphate reducing bacteria and CO2. - De Turris, Antonio; de Romero, Matilde; Papavinasam, Sankara (Rev. Téc. Fac. Ing. Univ. Zulia)
Â Under certain conditions, hydrocarbons may alter the internal corrosion conditions of oil and gas pipelines. In this paper, the effects of a crude oil have been analyzed using the ASTM G205 Standard Guide. The emulsion inversion point (EIP), the wettability of the steel surface and the effect of crude oil on the general and localized corrosion of carbon steel in synthetic produced water with sulfate-reducing bacteria (SRB) and carbon dioxide (CO2) was investigated. The EIP was determined measuring the resistance of the emulsion water/crude oil, and the Wettability was determined measuring the resistance by the spreading method. Corrosiveness experiments of aqueous phase were carried out in a Rotating Cage Apparatus. During the experiments the pH, planktonic bacterial count, and concentrations of sulphide, sulphate, iron, calcium and magnesium ions in the solution were measured. After the experiment, sessile bacterial count and mass loss of carbon steel was determined; corrosion products on the metal surface were identified using X-ray diffraction, and corrosion morphology was determined using a scanning electron microscope, optical microscope and laser profilometer. The experimental results show that the crude oil evaluated has a 50% EIP, a Mixed-Wet Wettability and is an Inhibitive Hydrocarbon because reduced de corrosion rate in 30%.